Descentralizacion forestal y estrategias de vida en Guatemala - Larson, A.M.; Miguel Barrios, J. (CIFOR and IDRC, 2006)
In this book, CIFOR explores the trends, opportunities, problems and challenges of forest decentralization in Guatemala, identifying its consequences particularly for its rural indigenous population and small-scale foresters, and proposing a research and action agenda that would promote increased equity of benefits from such processes. This publication is one of the outputs of a larger CIFOR study also carried in Bolivia, Brazil, Nicaragua and Honduras, which investigates forestry decentralization processes and, in particular, their effects on forest-dependent groups. The Guatemalan case study demonstrates that, more than in other countries, many municipal governments play an important role in forest resources management, creating the opportunity to promote forest-related issues within local administrations and to increase their capacity to manage natural resources. Nevertheless, the tensions between the state and other professional foresters’ vision of forests and forestry and that of an important sector of the indigenous population have not been addressed with the necessary respect for the latter, contributing to the ongoing marginalization of these groups. To support this analysis, this publication presents data on Guatemala’s forestry sector, the national context of financial, administrative and political decentralization, the implementation of forest and decentralization policies, focusing on local governance, and the implications of decentralization for marginalized groups.